The impact of ignored negligible losses in engineering design: Baerodynamic drag on ET425M high speed train as study case / Muhammad Hafizuddin Zainal Abidin - Muhammad Hafizuddin , Zainal Abidin (2019)
ET425M high speed train built by Siemens for Express Rail Link to operate between Kuala Lumpur Sentral station to Kuala Lumpur International Airport. ET425M air conditioning units that installed on the roof section not incorporated with any air deflector design to mitigate additional air resistance. The additional drag resistance adds to train motion resistance that leads to higher traction effort thus conclude to additional power consumption. With using Ansys Fluent solver, the drag force, drag coefficient and max pressure acts on the original air conditioning unit design of ET425M is determined and compared with introduction of air deflector with various angle. With introduction of air deflector with angle of 20 degree, the drag force showed reduction of 27% reduction of drag force, 29% reduction of drag coefficient and 46% reduction of max pressure when train simulated moving at train velocity of 160Km/h. With using approximation and assumption method by comparing the difference of tractive effort to determine the relationship between reductions of air resistance with power consumption, a reduction of 3% is achieved which translated to saving of RM 7,458,674 for operation of 30 years with current train operation frequency.